Kontribusi Usaha Madu Kelulut Terhadap Pendapatan Anggota Kelompok Usaha Perhutanan Sosial di Desa Bahu Palawa: The Contribution of Kelulut Honey Business to the Income of Members of Social Forestry Business Groups in Bahu Palawa Village - Birawa, Cakra; Nursiah, Nursiah; Wibowo, Agung; Penyang, Penyang; Zega, Mega Plena (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The large contribution of the kelulut honey business to the income of households or farmer families can help family income. Bahu Palawa Village has formed a Social Forestry Business Group (KUPS) that cultivates kelulut honey, but until now it is not clear how the contribution of the kelulut honey business to the income of farmer groups in Bahu Palawa Village. This study was conducted to see how much contribution kelulut honey cultivation makes to the household income of farmers in Bahu Palawa Village. This study aims to analyze the contribution of income from the kelulut honey business and analyze the problems faced by the Kelulut honey KUPS in Bahu Palawa Village. The method used is a census of KUPS members as many as 17 respondents where their income and income will be analyzed. The results obtained from the research conducted are the income of members in KUPS with an average of Rp. Rp.1.088.259/family/year with a total of 17 members. The income of members outside the KUPS is honey kelulut with an average of Rp.6.294.118/family/year. The contribution of income in KUPS from 17 members of the contribution group of 1.74% is included in the very insufficient category. The problems faced include uncertain weather factors such as high rainfall that reduces bee activities, obstacles in marketing due to lack of market reach and effective promotional strategies, and business management that is still simple with limitations in production planning, human resources, raw materials, and business capital.